2008
DOI: 10.1590/s1413-35552008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Influência da fisioterapia complexa descongestiva associada à ingestão de triglicerídeos de cadeia média no tratamento do linfedema de membro superior

Abstract: Objective: To investigate the influence of complex decongestive physical therapy (CDP) in association with diet therapy using mediumchain triglycerides (MCT), as an intervention in cases of upper-limb lymphedema. Methods: The lymphedema was evaluated by measuring circumferences, volumes, skin folds and whole-body water content. Feelings of discomfort, pain and heaviness in the arms were evaluated using a visual analog scale. Ten women who had undergone mastectomy and presented upper-limb lymphedema homolateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
20

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 13 publications
0
3
0
20
Order By: Relevance
“…Studies used all of its components (8)(9)(13)(14) or part of them (6,(15)(16)(17) . Applied to 36 women with post-surgical upper limb lymphedema, the CDT led to a mean reduction of 30.5% in the limb volume after the intensive phase, which was maintained during the studied periods (8) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies used all of its components (8)(9)(13)(14) or part of them (6,(15)(16)(17) . Applied to 36 women with post-surgical upper limb lymphedema, the CDT led to a mean reduction of 30.5% in the limb volume after the intensive phase, which was maintained during the studied periods (8) .…”
Section: Resultsmentioning
confidence: 99%
“…The assessment involved circumference and volume measurement, bioimpedance, cutaneous folds and visual analogue scale for feeling of discomfort. It was concluded that physiotherapy, together with the intake of medium-chain triglycerides (MCT), effectively acted on the involution of the disease, particularly in terms of circumference, volume and feeling of heaviness (15) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A gestão do linfedema é multidisciplinar, exigindo a atuação de vários profissionais da área da saúde em diferentes estágios da doença, incluindo: especialista em linfologia, psicólogo, fisioterapeuta, médico geneticista e, em alguns casos, um cirurgião especialista em distúrbios linfáticos 5 . Na área da nutrição há relatos de que o uso de triglicerídeos de cadeia média (TCM), associado com outros métodos, pode ajudar na redução do linfedema 8 . O tratamento do linfedema deve ser mantido por toda a vida, por se tratar de uma doença crônica, sendo a reabilitação um processo muito importante, porque é um recurso que procura prevenir e minimizar as incapacidades adquiridas, promover a maior funcionalidade possível e desenvolver o potencial psicossocial 1,8 .…”
Section: Introductionunclassified
“…Na área da nutrição há relatos de que o uso de triglicerídeos de cadeia média (TCM), associado com outros métodos, pode ajudar na redução do linfedema 8 . O tratamento do linfedema deve ser mantido por toda a vida, por se tratar de uma doença crônica, sendo a reabilitação um processo muito importante, porque é um recurso que procura prevenir e minimizar as incapacidades adquiridas, promover a maior funcionalidade possível e desenvolver o potencial psicossocial 1,8 . O presente artigo apresenta o tema cuidado nutricional no linfedema, embasado na literatura científica.…”
Section: Introductionunclassified